2011
DOI: 10.1038/jp.2011.133
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of rapid phIGFBP-I assay for predicting preterm labor in symptomatic patients

Abstract: Objective: To estimate sensitivity, specificity, positive and negative predictive values (PPV, NPV) of insulin-like growth factor binding protein-1 (phIGFBP-1) test in predicting preterm delivery in women with symptoms of preterm labor. Secondary objectives were to compare test characteristics of the phIGFBP-1 and fetal fibronectin (fFN) tests.Study Design: Labor and delivery units in two Calgary hospitals. Subjects were 349 women with suspected labor between 24 and 35 weeks gestational age (GA). Women had cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Phosphorylated IGFBP-1 is produced by the uterine decidua and the concentration of phosphorylated IGFBP-1 has been used as a marker for preterm labor [31]. IGFBP-1 thus seems to have several important roles during pregnancy from implantation to delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated IGFBP-1 is produced by the uterine decidua and the concentration of phosphorylated IGFBP-1 has been used as a marker for preterm labor [31]. IGFBP-1 thus seems to have several important roles during pregnancy from implantation to delivery.…”
Section: Discussionmentioning
confidence: 99%
“…These tests, however, have limited application in identifying women who will deliver preterm, because of their relatively low sensitivity and poor positive predictive values (PPVs). 5,6 In contrast, their utility relies on their high negative predictive value (NPV) in recognising women who are unlikely to deliver preterm.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent prospective observational study confirmed high NPV, but poor PPV, for preterm birth within seven days or two weeks (table). 10 The test is cheaper than fetal fibronectin, and the high NPV supports its use as a "rule out" test (directing resources and treatment away from women at low risk), rather than for positive prediction.…”
Section: Phosphorylated Insulin-like Growth Factor Binding Proteinmentioning
confidence: 99%